2018
DOI: 10.1016/j.ajme.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-C Virus Infection and Exposure to Blood and Body Fluids among Nurses and Paramedical Personnel at the Alexandria University Hospitals, Egypt

Abstract: Background: Worldwide, prevalence of anti-HCV positivity in health care workers (HCWs) ranges from 0% to 9.7%. The current study was conducted to calculate prevalence of HCV infection, frequency and characteristics of blood and body fluid (BBF) exposure among HCW at the Alexandria University Hospitals. Methods: Hospital-based cross-sectional approach was adopted. At the Hospitals, 62.2% of available nurses and paramedical personnel voluntarily participated (n = 499), and were interviewed, screened for HCV anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…(20) Some authors found that technicians and nurses were more affected. (21)(22)(23) This variation may be attributed to differences in the nature and duration of exposure in different settings as well as different sample sizes and population demographics. Participants with an employment duration of more than 10 years had a high proportion of positive HCV-Ab compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Some authors found that technicians and nurses were more affected. (21)(22)(23) This variation may be attributed to differences in the nature and duration of exposure in different settings as well as different sample sizes and population demographics. Participants with an employment duration of more than 10 years had a high proportion of positive HCV-Ab compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…In health care settings, transmission of HBV and HCV has been documented from patient to medical personnel, from medical personnel to patient, and from patient to patient [8]. Medical personnel are highly exposed to infection risk due to injuries from contaminated sharp surgical instruments, such as needles or blades [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals as labor-, expert-, capital-, and technology-intensive service industries which also have potential hazards and complexity of risks that increase the incidence of workplace accidents or occupational diseases. Based on previous research, so many risks could happen in hospital activities like drug administration error, incorrect operation of medical equipment, error in patient identification, needle stick injuries, work-related disease from sharp injuries at night duty, blood exposure, splash exposure, body fluids exposure among health care, and occupational safety precautions among nurses [2], [3], [4], [5], [6]. All of these risks can ktisptif the cause is due to the behavior of health provider themselves in managing medical or nonmedical waste.…”
Section: Introductionmentioning
confidence: 99%